EFFECTIVE INDICATORS FOR ATTRACTING FOREIGN INVESTMENT (World Economics and Finance Bulletin, 2024)
This article discusses the effective organization of investment activities in the economy, accelerating the expansion of our economic capabilities, and employing our internal capabilities and reserves.
Keywords: Investments; financial resources; taxes